2018
DOI: 10.3389/fnmol.2018.00246
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Isolation Elicits Depression and Anxiety-Related Behaviors by Reducing Oxytocin-Induced GABAergic Transmission in Central Amygdala

Abstract: Isolation stress is a major risk factor for neuropsychiatric disorders such as depressive and anxiety disorders. However, the molecular mechanisms underlying isolation-induced neuropsychiatric disorders remain elusive. In the present study, we investigated the subcellular mechanisms by which long-term isolation elicits depression and anxiety-related behaviors in mice. First, we found that long-term isolation induced depression-related behaviors in the forced swimming test (FST) and the sucrose preference test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 53 publications
0
54
0
1
Order By: Relevance
“…Converging reports on stress‐induced GABA and glutamate dysfunction have shown that the impaired balance of neural excitation and inhibition is a characteristic feature of depression pathophysiology . In addition, novel rapid‐acting agents and allosteric modulators of glutamate or GABA receptor complexes can reset both excitatory and inhibitory neurotransmitter systems . The neurotrophin signaling, MAPK and PI3K‐Akt signaling pathways were closely related to the BDNF/TrkB‐dependent PI3K/Akt/mTOR1 pathway, according to the pathway diagram provided by the KEGG database.…”
Section: Discussionmentioning
confidence: 99%
“…Converging reports on stress‐induced GABA and glutamate dysfunction have shown that the impaired balance of neural excitation and inhibition is a characteristic feature of depression pathophysiology . In addition, novel rapid‐acting agents and allosteric modulators of glutamate or GABA receptor complexes can reset both excitatory and inhibitory neurotransmitter systems . The neurotrophin signaling, MAPK and PI3K‐Akt signaling pathways were closely related to the BDNF/TrkB‐dependent PI3K/Akt/mTOR1 pathway, according to the pathway diagram provided by the KEGG database.…”
Section: Discussionmentioning
confidence: 99%
“…102 Administration of oxytocin into the central amygdala has also been shown to reduce anxiety-related behaviour in female rats. 102 Administration of oxytocin into the central amygdala has also been shown to reduce anxiety-related behaviour in female rats.…”
Section: Central Amygdalamentioning
confidence: 99%
“…Activation of the oxytocin receptor in the central amygdala has been reported to reverse isolation stress-induced anxiety-related behaviour in mice. 102 Administration of oxytocin into the central amygdala has also been shown to reduce anxiety-related behaviour in female rats. 103 Oxytocin has also been suggested to reduce conditioned fear- On the other hand, contradictory findings have also been reported.…”
Section: Central Amygdalamentioning
confidence: 99%
“…Oxytocin-synthesizing neurons in the PVN project long-range axonal terminals to the CeL, where the local release of oxytocin directly regulates anxiety levels (35,36), fear memories and fear extinction (37,38). Moreover, a recent study highlighted the pivotal role of oxytocin signaling in the CeA in mouse models of depression (39). While neuroin ammation in the PVN of HF rats has been previously described (25,26), it is at present unknown whether HF-induced neuroin ammation in other brain areas, such as the CeA also occurs, and if so, how it temporally relates to the onset of neuroin ammation in the PVN.…”
Section: Introductionmentioning
confidence: 99%